Entre o cuidar e o sofrer: o cuidado do cuidador via experiência de cuidadores/profissionais de saúde mental - Alves, Carlos Frederico de Oliveira (2005)
Due to the recent transformations in the scenery of the attendance in public health in our country, fruit of the Sanitary Reform and beginning of the Only System of Health (SUS), in the end of the decade of 80, it is noticed the need of amplification of studies understood the professionals' dynamics involved in this process again. In this context, they interfere the actions in mental health, based on the presuppositions of the Brazilian Psychiatric Reform. Like this being and before the lack of studies concerning this reality, the accomplishment of this study was looked for with the objective of understanding as it is had given the these professionals' praxis, with emphasis in the subject of the worker's health, as manifestation of an attitude of the caretaker's care. The scenery that permeates the day by day of the workers of health aims us subjects concerning the relationship suffering/care for besides a dynamics strictly intra-psychic, crossed, in whole moment, for a series of subjects of stamp social-psychic and institutional. In this sense and starting from an approach with the logic and guidelines that the operation of the services and models of the attendance in the ambit of the Attention to the Mental Health in the context of SUS, an amplification of the understanding of the stress was looked for in the work and, more specifically, of the Syndrome of Burnout, as possible indicators of the suffering panorama in which interfere these subjects. The approach of this problematic one allowed the ransom of the implication of subjects related to the modern vision of technique, to the processes of construction of the caretaker's social image, to the professional formation and, finally, to the relationship among anguish and care in its existential aspects. Starting from a positioning of the existential phenomenological, as attitude of to be and to research, they were picked narratives, while reports of lived experience, of professionals inserted in this net of services of attendance. The depositions pointed, among other subjects, aspects related to the transitory character and, per times, paradoxical, in that she meets the formation of the substitution net in Mental Health, with emphasis in the painful existences, fruit of the discrepancy between the professional's expectation and institutional conditions. Before this, it discusses him that, starting from the complexity implied in the situation of the caretakers' negligence, she makes himself necessary the maintenance of the tension among the several involved aspects, as well as the constant rising of subjects of the paper of each element of the system, in a care attitude that implies them collectively ambit of the care while ethical and political attitude, crossed by the care of itself, the institutional care and the care of the another